An overview of the use of central venous catheters impregnated with drugs or with inorganic nanoparticles as a strategy in preventing infections - Corrêa Carvalho, Gabriela [UNESP]; Miguel Sábio, Rafael [UNESP]; Spósito, Larissa [UNESP]; de Jesus Andreoli Pinto, Terezinha; Chorilli, Marlus [UNESP] (Elsevier, 2022)
Central venous catheter (CVC) is a medical device widely used in therapeutics to avoid repetitive venipuncture. Although its use is advantageous, it is possible to highlight limitations, such as the risk of catheter-related bloodstream infections, caused by excessive manipulation and even the urgency at the time of insertion. These factors lead to an expensive treatment, often hampered by resistance to antimicrobial agents, exposing the patient the risk and even leading to death. The use of CVC impregnated with free drugs or incorporated with nanoparticles is a promising strategy for preventing the adherence of microorganisms in these devices and consequently in the prevention of the infections. Although most of the nanoparticles registered by the FDA for medical use are organic, several studies have reported the potential of inorganic nanoparticles for this purpose. Therefore, the present review seeks to highlight the current scenario of hospital infections related to the use of CVC and the importance of CVCs impregnated with drugs or incorporated with inorganic nanoparticles as an interesting strategy in combating infections assigned to the use of this medical device.
Keywords: Antimicrobials; Catheter-related bloodstream infections; Central venous catheter; Hospital infection; Inorganic nanoparticles